Fire strike [compact disc, unabridged] - Cussler, Clive; Maden, Mike (Cussler, Clive. Oregon files adventures., 2023)
Juan Cabrillo and the crew of the Oregon must battle an army of genetically engineered mercenaries to stop a hypersonic missile attack before the Arabian Sea becomes a mass grave.